1987
DOI: 10.1002/aic.690330309
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent diffusion in concentrated electrolyte solutions: Effect of solvation

Abstract: A method is presented to estimate the diffusivities of electrolytes in concentrated multicomponent systems. The method is based on the Stefan-Maxwell flux equations. Explicit expressions have been developed for the phenomenological transport coefficients. These expressions incorporate the effects of solvation, viscosity, and ionic interactions. It has been shown that multicomponent diffusion behavior can be related to corresponding single-electrolyte and tracer diffusion cases. Thus, solvation effects are esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…An extensive literature review revealed that numerous papers report diffusion coefficients for aqueous potassium chloride solutions, but most of them are measured at ambient conditions and for dilute solutions. The majority of the studies relating to diffusion in aqueous solutions of electrolytes are concerned with the development of reliable techniques for the measurement of the concentration dependence .…”
Section: Introductionmentioning
confidence: 99%
“…An extensive literature review revealed that numerous papers report diffusion coefficients for aqueous potassium chloride solutions, but most of them are measured at ambient conditions and for dilute solutions. The majority of the studies relating to diffusion in aqueous solutions of electrolytes are concerned with the development of reliable techniques for the measurement of the concentration dependence .…”
Section: Introductionmentioning
confidence: 99%
“…For eq 5, the binary constant gi; is determined by using our earlier approach (1987). The value of gNaK has already been determined as 1.97 (Pinto and Graham, 1987). From tracer diffusion data for Na+ in NaCl and LiCl solutions (Robinson and Stokes, 1968), the values of gNaNa and gNaLi were calculated to be 1.92 and 2.46, respectively.…”
Section: Resultsmentioning
confidence: 98%
“…Conventionally, in treating tracer diffusion, solvation is neglected. However, Pinto and Graham (1987) have shown that for electrolyte solutions this assumption may not be valid. In terms of solvated species, eq 13 takes the form For the ternary system being considered, this equation *f i1…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multicomponent mass transfer at a fluid and solid interface can be found in many chemical engineering processes such as leaching, dissolution or crystallization, electrolysis, and adsorption, as well as chemical reactions involving solid reactants or porous catalysts. Consequently, it has long been a focus of studies in many different disciplines (Wendt, 1965;Woolf, 1972;Stewart and Prober, 1964;Stewart, 1973;Cussler, 1976;Anderson and Graf, 1976;Taylor, 1982;Smith and Taylor, 1983;Pinto and Graham, 1987). But most of the previous work centered either on the sole aspect of multicomponent diffusion or on the mathematical treatments of convective processes under welldefined conditions.…”
Section: Introductionmentioning
confidence: 99%